Kualitas Fisik, Mikrobiologi dan Organoleptik Sosis Ayam Komersil yang Beredar di Tempat Berbeda di Bogor - Yusuf, M.; Wihansah, R. R. S.; Arifin, M.; Oktaviana, A. Y.; Rifkhan, Rifkhan; Negara, J. K.; Sio, A. K. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
This study aimed to evaluate the quality of physical, microbiological and organoleptic chicken sausage around on campus IPB, Bogor to evaluate its feasibility. Chicken sausage samples obtained from two groups of different markets, namely supermarket and traditional market. The design of the treatment of this study consisted of two treatment that sausage that comes from the traditional markets (stored at room temperature) and sausage that comes from the supermarket (stored at cold temperatures) and each market was taken a sample of three replications. The physical quality was observed pH and aw, while the microbiological quality was observed quantitative testing total microbial colonies (PCA), E. coli, Salmonella sp, Staphylococcus aureus, according to the BSN (2008) and FDA method (1998). Organoleptic quality chicken sausage test was using hedonic test. The results showed that the chicken sausages in the market around the campus of IPB was still feasible for consumption due to microbial contamination was still low compared with SNI and organoleptic sausage was still accepted by the panelists